PENGARUH MEDIA GAME KOMPUTER TERHADAP PEMBELAJARAN KOSAKATA BAHASA INGGRIS PADA ANAK REMAJA - Pramono, Johanes Gilang (Kajian Linguistik, 2018)
The purpose of this reaserch is to find out English vocabulary learning process from youth when they play computer game. The method of this research is descriptive qualitative methodwhich collecting data throgh process observe and semi-structured interview. The result of this research is some English vocabulary learning process occur from elements of multimedia inside game such as picture, sound, and animation. The conclusion of this research is English vocabulary learning process from media computer game occur based from motivation of completing mission in the game so that vocabulary learning process occur in pleasing atmosphere.Keywords: Learning, Vocabulary, English, Media, Game, Komputer